ISO 9001 certification pay-off: myth versus reality - Sampaio, Paulo (2012)
Purpose – Despite all the studies carried out in order to analyze the impact of quality management systems’ implementation and certification on companies’ financial performance, conclusions reached so far have a contradictory nature. Some authors conclude that there is a positive relationship between ISO 9001 certification and companies’ financial improvement, while others do not find evidence to support such a relationship. The purpose of this paper is to present the main results derived from a research project developed in order to analyze the economical impact of quality management system implementation and certification on companies’ performance. Design/methodology/approach – This paper describes the results obtained from studying the economic impact of quality management systems, based on the adoption of a case study methodology. The authors’ goal was to reconstruct the companies’ financial history with the aim of identifying the benefits and costs directly related to their quality management systems. The analyzed time period ranged from the year when the company decided to implement its quality management system up to the present. Findings – Results show that it is not unanimous that certified companies would be less profitable if they had not implemented their quality management systems. Originality/value – This paper tries to be an important contribution to the worldwide research related to the quality management systems’ impact on companies’ financial performance.